Cross-cultural validation and psychometric testing of the Norwegian version of the TeamSTEPPS® teamwork perceptions questionnaire - Randi Ballangrud; Sissel Eikeland Husebø; Marie Louise Hall-Lord (BMC, 2017)
Abstract Background Teamwork is an integrated part of today's specialized and complex healthcare and essential to patient safety, and is considered as a core competency to improve twenty-first century healthcare. Teamwork measurements and evaluations show promising results to promote good team performance, and are recommended for identifying areas for improvement. The validated TeamSTEPPS® Teamwork Perception Questionnaire (T-TPQ) was found suitable for cross-cultural validation and testing in a Norwegian context. T-TPQ is a self-report survey that examines five dimensions of perception of teamwork within healthcare settings. The aim of the study was to translate and cross-validate the T-TPQ into Norwegian, and test the questionnaire for psychometric properties among healthcare personnel. Methods The T-TPQ was translated and adapted to a Norwegian context according to a model of a back-translation process. A total of 247 healthcare personnel representing different professionals and hospital settings responded to the questionnaire. A confirmatory factor analysis was carried out to test the factor structure. Cronbach's alpha was used to establish internal consistency, and an Intraclass Correlation Coefficient was used to assess the test - retest reliability. Result A confirmatory factor analysis showed an acceptable fitting model (χ2 (df) 969.46 (546), p < 0.001, Root Mean Square Error of Approximation (RMSEA) = 0.056, Tucker-Lewis Index (TLI) = 0.88, Comparative fit index (CFI) = 0.89, which indicates that each set of the items that was supposed to accompany each teamwork dimension clearly represents that specific construct. The Cronbach's alpha demonstrated acceptable values on the five subscales (0.786-0.844), and test-retest showed a reliability parameter, with Intraclass Correlation Coefficient scores from 0.672 to 0.852. Conclusion The Norwegian version of T-TPQ was considered to be acceptable regarding the validity and reliability for measuring Norwegian individual healthcare personnel's perception of group level teamwork within their unit. However, it needs to be further tested, preferably in a larger sample and in different clinical settings.